Influence of context on responsible leadership: evaluation in the two island nations of Maldives and Sri Lanka - Shakeela, Mariyam (Curtin University, 2009)
This study focused on elucidating leadership mindset towards responsible leadership, from the perspectives of national elite, and integrates them with corporate understanding. A multi-method and a pluralistic approach with in depth interviews and empirical survey were employed. Data was collected from eminent leaders who are either leading or led governments, held or hold ministries and diplomatic missions, and are controlling influences in leading business enterprises selected in the two Asian island nations of the Republic of Maldives and Sri Lanka. This research also explored the understanding, motivation and experience base of the strategic leaders. Caution may need to be exercised in interpreting the findings as some of the fundamental philosophies and practices are often embedded in the societal heritage, and accumulated experiences passed through family or organisational successions.The findings of this study suggest that responsible leadership is often determined by the imperatives of contextual complexity. The competencies, values and experiences, and a series of other factors matter significantly. However, while context plays a major role, the perception of the elite leaders suggest exercising caution to the fact that contextual factors do not influence as a standalone force, but rather as an interacting phenomenon. Therefore, the behaviour that transpires is always unique. To attain responsible leadership, what is required is a confident leader, working in a learning environment, with the right emotional competencies to deal with the changing times, multicultural and diversified workforce, within a flexible yet controlled environment to attain the greatest good for the greatest number of people. While having many common elements, leadership behaviour across gender and nationalities differed, reflecting their past, the changing times, prevailing circumstances and the organisational priorities. While female leaders of Sri Lanka and Maldives are not any different from men in their ability to lead, use a unique combination of skills and approaches contingent on context, as they work within a complex interaction and tug-of war between cultural conservatism and the rapid advancement in knowledge, skills opportunities and the need for responsible leadership.